APPLICATION AND INTERPRETATION OF THE AGREEMENT ON ENHANCING INTERNATIONAL ARCTIC SCIENTIFIC COOPERATION - P. A. BERKMAN; A. N. VYLEGZHANIN; O. R. YOUNG (Московский журнал международного права, 2018)
INTRODUCTION. The Agreement on Enhancing International Arctic Scientific Cooperation, 2017, has recently become part of the International Law applicable to the Arctic Region and the relevant legal history is considered in this paper. Special attention is paid to the scope of application of the 2017 Agreement and the interpretation of provisions which provide new rights and obligations of its Parties in the context of an extensive international legal framework which already applies to the Arctic Ocean.Materials and Methods. The materials for research include first and foremost the text of the 2017 Arctic Agreement, in the context of other rules of International Law, both treaty and customary, which are applicable to the Arctic Ocean. General and special scientific methods of contemporary cognition composed the relevant methodological basis for the research.RESEARCH RESULTS. The 2017 Arctic Agreement has become an important element of the extensive international legal framework which applies to the Arctic Ocean. This broad international legal framework is contained in a system of International Law instruments regulating relations between subjects of International Law: first of all, between Arctic States, and then between them and non-Arctic States; especially in such branches of States’ activity as the protection of the marine environment, including ice-covered areas, freedom of navigation, marine scientific research, and other uses of the sea. Within this extensive legal framework the 2017 Agreement has a special position as lex posterior. This is important in the context of the scope of the Agreement (the designated territories of the Parties) and also taking into account the complexity of its correct interpretation.DISCUSSION AND CONCLUSION. Science cooperation according to the 2017 Arctic Agreement may contribute to improving regulatory measures in a number of vital areas: to promote best available technologies in the Arctic region; to make more safe navigation in the Arctic waters (while they are becoming free from ice during most of the year); to assist in formulating modern maps for Arctic navigation; to advance plans for creating modern port infrastructure in the North ; science cooperation might give impetus to designating new sea lanes and traffic separation schemes (in the Barents Sea and in the Bering Strait, for example) and to promote additional legal measures to protect and preserve the marine environment in the Arctic.